Admission Serum Calcium Level and Short-Term Mortality After Acute Ischemic Stroke: A Secondary Analysis Based on a Norwegian Retrospective Cohort - Lu, Yuzhao; Ma, Xin; Tazmini, Kiarash; Yang, Ming; Zhou, Xiaobing; Wang, Yang (Frontiers in Neurology, 2022)
Background Disturbed serum calcium levels are related to the risk of stroke. However, previous studies exploring the correlation between serum calcium and the clinical outcome of ischemic stroke (IS) have shown inconsistent results. Object The study aimed to investigate the relationship between admission serum calcium and 30-day mortality in patients with IS. Methods A total of 876 IS patients from a Norwegian retrospective cohort were included for secondary analysis. The exposure variable and the primary outcome were albumin-corrected serum calcium (ACSC) at baseline and all-cause mortality within 30 days after the first admission, respectively. Multivariable logistic regression analysis was used to estimate the risk of 30-day mortality according to ACSC levels. Moreover, the potential presence of a non-linear relationship was evaluated using two-piecewise linear regression with a smoothing function and threshold level analysis. The stability of the results was evaluated by unadjusted and adjusted models. Results The result of multiple regression analysis showed that ACSC at baseline was positively associated with the incidence of 30-day mortality after adjusting for the potential confounders (age, gender, serum glucose, hypertension, atrial fibrillation/atrial flutter, renal insufficiency, heart failure, chronic obstructive pulmonary disease, pneumonia, paralysis, and aphasia) (OR = 2.43, 95% CI 1.43–4.12). When ACSC was translated into a categorical variable, the ORs and 95% CIs in the second to the fourth quartile vs. the first quartile were 1.23 (0.56, 2.69), 1.16 (0.51, 2.65), and 2.13 (1.04, 4.38), respectively (P for trend = 0.03). Moreover, the results of two-piecewise linear regression and curve-fitting revealed a linear relationship between ACSC and 30-day mortality. Conclusion ACSC is positively associated with 30-day mortality in IS patients, and the relationship between them is linear.